Desfechos clínicos do tratamento de tuberculose utilizando esquema RHZE em comprimidos com dose fixa combinada - Ferreira, Anna Carolina Galvão (2012)
OBJECTIVE: To describe tuberculosis treatment rates of cure, failure and default of a self administered regimen, with rifampin, isoniazid, pyrazinamide and ethambutol in the first two months of treatment followed by isoniazid and rifampcina in the four last months (2RHZE/4RH) in four-drug fixed-dose combination (FDC), implemented in Brazil since 2010 to replace a regimen of separately administered rifampicin, isoniazid and pyrazinamide in the first two months of treatment followed by isoniazid and rifampcina for four months (2RHZ/4RH). METHODS: Descriptive study using prospectively collected data from medical records of TB cases, older than18 years of age undergoing treatment with 2RHZE/4RH in two units of primary health care in the metropolitan area of Goiânia. RESULTS: The study included 40 cases of TB. The cure rate was 67.5% (27/40), the abandonment was 17.5% (7/40) and there were no cases of failure. There was reports of adverse reactions in 47% (19/40) of the cases. Of these, 87% were mild and 13% were moderate. There was no need for change or suspension of the scheme. CONCLUSIONS: The cure rate in FDC 4RHZE/2RH scheme under self-administered regimen was similar to historical rates of cure with 2RHZ/4RH. The default rate in the sample studied was much higher than the rate recommended as appropriate (up to 5%).